Takhrij Al-Hadits Sebagai Basis Istinbat Hukum : Telaah Historis Dan Metodologis - Sopyan, Muh.; Ahmad, La Ode Ismail (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Hadith is the second source of Islamic teachings after the Qur'an. However, unlike the Qur'an, Hadith requires in-depth research to determine its quality due to the dynamics in the transmission process (sanad) and the text content (matan). This study aims to examine the urgency, history, and methodology of takhrij al-hadith as a vital instrument in determining whether a hadith is maqbul (accepted) or mardud (rejected). The research method used is library research with content analysis techniques on primary and secondary literature in the field of Ulumul Hadith. The results show that takhrij is a method of tracing hadith to its original source (the primary books) by explaining the chain of transmission and its quality. There are five main methods in takhrij: (1) based on the first word of the matan, (2) through keywords (bi al-lafzh), (3) based on the theme (bi al-maudhu’), (4) based on the first narrator (bi al-rawi al-a'la), and (5) based on the specific attributes or status of the hadith. The urgency of takhrij lies in its ability to preserve the purity of Islamic teachings from fabricated narrations, clarify obscure chains of transmission, and provide a solid foundation for Muslims in practicing a hadith.